Collective Leadership Model in Improving the Target of Development of Islamic Boarding School Educational Institutions: Model Kepemimpinan Kolektif Dalam Meningkatkan Target Pengembangan Lembaga Pendidikan Pondok Pesantren - Choiroer Rofiq; Yayuk Fauziyah (Academia Open, 2021)
The collective leadership model is very influential in the implementation of the development of educational institutions, basically the implementation of this collective leadership model is the division of tasks and positions as a whole with the shared authority and responsibility.This study describes the collective leadership model in increasing the target for the development of the An Nur Penatarsewu Islamic boarding school Tanggulangin Sidoarjo educational institution, the focus of the research is the collective leadership model, its implementation, "supporting and inhibiting factors" in the implementation of the development of Islamic boarding school educational institutions.The choice of research method in describing it using qualitative methods. Researchers collect data by means of observation, interviews and documentation. The validity of the data was tested by triangulating the data, examining the suitability of the written data, the results of interviews and observations that had been made.This research produces findings. First, the An Nur Penatarsewu Islamic boarding school uses a collective leadership model in developing educational institutions by means of: planning, monitoring and evaluation. The decision-making system of the An Nur Islamic Boarding School is by way of deliberation and consensus by taking steps; identification of problems, gathering information, predicting the consequences that will occur, alternative decisions Second, the collective leadership of the An Nur Islamic boarding school carries out the duties and responsibilities shared by each other. Third, the application of collective leadership is driven by a sense of togetherness in developing the An Nur Islamic boarding school educational institution.